Coral Oxygen Isotopic Records Capture the 2015/2016 El Niño Event in the Central Equatorial Pacific. Issue 24 (20th December 2021) - O'Connor, Gemma K.; Cobb, Kim M.; Sayani, Hussein R.; Atwood, Alyssa R.; Grothe, Pamela R.; Stevenson, Samantha; Baum, Julia K.; Chen, Tianran; Claar, Danielle C.; Hitt, Nicholas T.; Lynch‐Stieglitz, Jean; Mortlock, Richard A.; et al.
Abstract: Coral oxygen isotopes (δ 18 O) from the central equatorial Pacific provide monthly resolved records of El Niño‐Southern Oscillation activity over past centuries to millennia. However, calibration studies using in situ data to assess the relative contributions of warming and freshening to coral δ 18 O records are exceedingly rare. Furthermore, the fidelity of coral δ 18 O records under the most severe thermal stress events is difficult to assess. Here, we present six coral δ 18 O records and in situ temperature, salinity, and seawater δ 18 O data from Kiritimati Island (2°N, 157°W) spanning the very strong 2015/16 El Niño event. Local sea surface temperature (SST) anomalies of +2.4 ± 0.4°C and seawater δ 18 O anomalies of −0.19 ± 0.02‰ contribute to the observed coral δ 18 O anomalies of −0.58 ± 0.05‰, consistent with a ∼70% contribution from SST and ∼30% from seawater δ 18 O. Our results demonstrate that Kiritimati coral δ 18 O records can provide reliable reconstructions even during the largest class of El Niño events. Plain Language Summary: Oxygen isotope anomalies in coral skeletons are a well‐established proxy for changes in tropical Pacific Ocean temperature variations, which have a profound impact on weather extremes around the planet. However, only a handful of calibrations exist that quantify the relationship between ocean temperature and coral oxygen isotopic composition at a given site, especially across extreme events where this relationship may vary most strongly. Here we compare ocean temperature data from loggers installed on the reef at Kiritimati Island (2°N, 157°W) to coral oxygen isotopic records spanning the record‐breaking 2015/16 El Niño event. We find that oxygen isotopes in corals provide accurate reconstructions of ocean temperature extremes during this very strong El Niño event, with ∼70% of the signal originating from ocean temperature and the remainder from increased rainfall. Key Points: An ensemble of coral oxygen isotope timeseries from the central equatorial Pacific tracks the 2015/16 El Niño event Coral oxygen isotope records reflect ∼70% contribution from warming and ∼30% from freshening during the 2015/16 El Niño event In situ seawater oxygen isotope data provide quantitative constraints on temperature versus hydrological contributions to coral records